Inflammatory bowel disease–associated intestinal fibrosis - Ji Min Park; Jeongseok Kim; Yoo Jin Lee; Sung Uk Bae; Hye Won Lee (Journal of Pathology and Translational Medicine, 2023)
Fibrosis is characterized by a proliferation of fibroblasts and excessive extracellular matrix following chronic inflammation, and this replacement of organ tissue with fibrotic tissue causes a loss of function. Inflammatory bowel disease (IBD) is a chronic inflammation of the gastrointestinal tract, and intestinal fibrosis is common in IBD patients, resulting in several complications that require surgery, such as a stricture or penetration. This review describes the pathogenesis and various factors involved in intestinal fibrosis in IBD, including cytokines, growth factors, epithelial-mesenchymal and endothelial-mesenchymal transitions, and gut microbiota. Furthermore, histopathologic findings and scoring systems used for stenosis in IBD are discussed, and differences in the fibrosis patterns of ulcerative colitis and Crohn’s disease are compared. Biomarkers and therapeutic agents targeting intestinal fibrosis are briefly mentioned at the end.